2007
DOI: 10.2337/dc06-1832
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Exposure and Self-Reported Gestational Diabetes Mellitus in the Agricultural Health Study

Abstract: OBJECTIVE -To examine the association between pesticide use during pregnancy and gestational diabetes mellitus (GDM) among wives of licensed pesticide applicators.RESEARCH DESIGN AND METHODS -Using data from the Agricultural Health Study (AHS), we estimated the association between self-reported pesticide-related activities during the first trimester of the most recent pregnancy and GDM among 11,273 women whose pregnancy occurred within 25 years of enrollment.RESULTS -A total of 506 (4.5%) women reported having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(106 citation statements)
references
References 30 publications
1
103
0
2
Order By: Relevance
“…Using data from the same nationally representative cross-sectional survey of the U.S. population, Navas-Acien and colleagues (2008) found that participants with type 2 diabetes had a 26% higher level of total arsenic (95% CI, 2.0-56.0) and the OR for type 2 diabetes comparing participants at the 80th versus the 20th percentiles was 3.58 for the level of urinary total arsenic (95% CI, 1.18-10.83). One previous study has shown an association with environmental exposures (agricultural pesticides) and increased risk of GD among wives of licensed pesticide applicators (Saldana et al 2007); however, that study relied on self-report of GD and pesticide usage.…”
Section: Discussionmentioning
confidence: 95%
“…Using data from the same nationally representative cross-sectional survey of the U.S. population, Navas-Acien and colleagues (2008) found that participants with type 2 diabetes had a 26% higher level of total arsenic (95% CI, 2.0-56.0) and the OR for type 2 diabetes comparing participants at the 80th versus the 20th percentiles was 3.58 for the level of urinary total arsenic (95% CI, 1.18-10.83). One previous study has shown an association with environmental exposures (agricultural pesticides) and increased risk of GD among wives of licensed pesticide applicators (Saldana et al 2007); however, that study relied on self-report of GD and pesticide usage.…”
Section: Discussionmentioning
confidence: 95%
“…Thus the Agricultural Health Study [9] examined 11,273 wives of licensed pesticide applicators, 506 (4.5%) of whom had gestational diabetes mellitus within 25 years of enrolment, while risk of diabetes was shown to be doubled in those involved in agricultural exposure during the first trimester of pregnancy. The Michigan PBB study (25 years of follow-up) showed increased incidence of diabetes in individuals with a PCB level >10.0 parts per billion (∼1,300 ng/g lipid) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports based on mortality rates analysis [6,7] or on self-reported diabetes also show associations between environmental pollution levels and prediabetes and/or diabetes [8][9][10]. However, in only few studies was diabetes diagnosed with the aid of fasting plasma glucose (FPG) (≥126 mg/dl [7.0 mmol/l]), HbA 1c (>6.1%) [9] or random glucose level (≥200 mg/dl=11.1 mmol/l) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Agricultural Health Study, women who reported agricultural pesticide exposure (by mixing or applying pesticides to crops or repairing pesticide application equipment) were twice as likely to develop gestational diabetes (odds ratio = 2.2 [95% confidence interval = 1.5 -3.3]) (Saldana et al 2007). The most recent findings from this prospective study of nearly 32,000 individuals showed that lifetime cumulative exposure to seven specific chlorinated pesticides increased the likelihood of diabetes (Montgomery et al 2008).…”
Section: Epidemiologic Trends In Diabetesmentioning
confidence: 99%